Highly Sensitive and Stable In Situ Acetylene Detection in Transformer Oil Using Polyimide-Embedded Carbon Nanotubes - Kim, Sihyeok; Choi, Jin Myung; Novikov, Ilya V.; Nam, Jeong Seok; Lee, Il hyun; Cai, Liang; Yoon, Jonghyuk; Lee, Yeounggyu; Lee, Jaehoon; Mikladal, Bjorn; Kang, Boseok; Kauppinen, Esko I.; et al. (Advanced Materials, 2024)
This study presents an acetylene gas sensor capable of in situ monitoring transformer oils. This sensor utilizes carbon nanotubes (CNTs) embedded in polyimide (PI) synthesized by floating catalyst chemical vapor deposition. Unlike conventional sensors that target hydrocarbon gases dissolved in oil and measure the gas extracted from the oil, the proposed CNT-PI sensor detects gas within the oil in real time. The PI embedding technique effectively anchors and shields the CNT network against fluidic damage, ensuring stable sensing performance over 6 months, even under friction stress caused by oil convection. Decorating CNTs with gold nanoparticles further enhances the sensitivity and response of the sensor. The sensor achieves a high response (10.5% at 30 ppm) and fast response/recovery times (28 s/77 s), Furthermore, the sensor demonstrates good response (10.4% at 30 ppm) and moderate response/recovery times (444 s/670 s) in an oil medium, which qualifies for industrial applications. Additionally, a CNT-PI-based heater is integrated into the sensor as a multilayer component, maintaining an optimal operating temperature of 90 °C. The CNT-PI sensor demonstrates consistent gas-sensing performance even after 10,000 bending cycles and exhibits superior characteristics, indicating its compatibility with various forms of transformers.
Keywords: C2H2 gas detector; C2H2 gas sensor; FCCVD; Fluid gas sensor; Gas-sensors; Oil gas; Oil gas sensor; Sensing performance; C2H2 gas detector; C2H2 gas sensor; carbon nanotubes; FCCVD; fluid gas sensor; oil gas sensor